Kajian Hadis-hadis Berkaitan Bersin Menurut Sunnah Nabi Muhammad - Muhammad Zuhdi Azman; Mohd Izzuddin Berzanji; Muhammad Fahmy Ariffin; Muhammad Akmalludin Mohd Hamdan (Academic Inspired Network, 2024)
Indexed by MyCite